INNOVATIONS IN ENGLISH LANGUAGE TEACHING AS AN IMPORTANT FACTOR OF MODERNIZATION AND IMPROVEMENT - Isgenderova Yegane Khaleddin (International Journal of Innovative Technologies in Social Science, 2024)
One of the general problems in the modern methodology of teaching the English language is the problem of improving and modernization of teaching. The intensify-cation of English language teaching involves the using of: modern forms and means of teaching; new methods of cognition in teaching: computers, audio, video and etc. The requirements for the modern educational process significantly exceed the using new methods of approaching the connection between teachers and learners, transforming of knowledge and ability with different methods of teaching. And all these help learners to improve their knowledge for connection in different conditions to present individual abilities. From this point of view nowadays, the main goal of teachers’ standard are not to teach the only science, but to teach of learning methods and ways. The analysis of this scientific article shows that, for learners improving innovation and modernization is the main feature of English language teaching. These methods increase the interest of teaching communication activities, the formation of listening and speaking skills on students for every foreign language teaching. As we know, many years ago, there were many problems on using of technology in education system. But nowadays, improving all kinds of technology and their using increase and all these help learners to get information on all spheres of language teaching ways, improve their thoughts on their skills and abilities. All these ways and methods take place in this article.